Academic education of Poles abroad. Tradition and new challenges on the 80th anniversary of PUNO - Perzycka, Elżbieta; Czubińska, Grażyna (Adult Education Discourses, 2020)
The everyday life of Poles living abroad is closely related to the tradition of their country of origin regardless of the elements that make up this life. Education and science play an important role in maintaining ties with the nation and the ethos of the Polish national heritage. This article undertakes the description of the conditions for implementing the academic education of Poles in exile and emigration, noting the importance of the activity of the Polish University Abroad for the traditions of Polish culture, education and science. The article also attempts to identify the mission and vision of academic education at the Polish University Abroad, as well as its present and future directions of development.